Pengaruh Obat Kumur Berbasis Fluoride Dan Essential Oils Terhadap Jumlah Angka Kuman Rongga Mulut - Lasmini, Titi (Universitas Mohammad Husni Thamrin, 2022)
Mouthwash is a solution or liquid that is used to clean the oral cavity with the aim of eliminating the bacteria causing tooth decay, working as a refresher and eliminating bad breath. The purpose of this study were to determine the differences of bacterial colony count in the oral cavity before and after using fluoride and essential oils based mouthwash, and to compare the effectiveness of both mouthwashes in reducing the number of oral bacteria. The sample for this study was mouth rinse collected from 10 students of Akademi Kesehatan John Paul II Pekanbaru, before and after using mouthwash. The samples were inoculated on Nutrient agar by pour plate method, and the bacterial colonies (CFU/mL) were counted after 2 days incubation.The results of this study showed that there was a difference of colony count between before and after the used of both mouthwashes. The mean of bacterial colony count after using fluoride-based mouthwash decreasedÂ by 314830.00 CFU/mL, whileÂ essential oils-based mouthwash reduced the bacterial colony count by 880220.00 CFU/mL. Dependent T-test showed that there were statistically significant reduction of bacterial colony count after the used of fluoride-based mouthwash (P=0.034) and essential oils-based mouthwash (P=0.008). Based on the Independent T-test there was no statistically significant difference (P>0.05) between fluoride and essential oils based mouthwash in reducing oral bacterial count.